Spatiotemporal patterns induced by cross-diffusion on vegetation model - Shuo Xu; Chunrui Zhang (AIMS Mathematics, 2022)
This paper considers the influence of cross-diffusion on semi-arid ecosystems based on simplified Hardenberg's reaction diffusion model. In the square region, we analyze the properties of this model and give the relaxation time correspond to the system to prejudge the approximate time of this system stabilization process. The numerical results are constant with the theory very well.